Imaging in urinary tract infection. Issue 11 (November 1991) - Gleeson, F V; Gordon, I
Abstract : The relationship of vesicoureteric reflex (VUR) and renal scarring was studied in 94 children (188 kidneys) with proved urinary tract infection in a district general hospital. There were 61 girls and 33 boys, with nine girls and 17 boys aged less than 1 year, 31 girls and nine boys aged between 1 and 5 years, the remaining 28 children were over 5 years of age. All children had a micturating cystourethrogram and a 99mTc (technetium) dimercaptosuccinic acid (DMSA) scan. Forty two of the 188 kidneys were scarred and 70 of the kidneys had VUR. Only 37.1% of the kidneys with reflux were scarred but 61.9% of the scarred kidneys had VUR. In children of less than 1 year, 48% of kidneys with VUR were scarred whereas 70.6% of scarred kidneys had reflux. In children between 1 and 5 years of age only 36.4% of kidneys with VUR were scarred but 63.2% of scarred kidneys had VUR. There is good correlation between the detection of a scarred kidney on DMSA and the presence of vesicoureteric reflux. However the detection of reflux particularly in children over 1 year of age shows poor correlation with renal scarring. This suggests that the primary imaging in children over 1 year of age presenting with a urinary tract infection should be of the kidney: a cystogram should be performed only if the DMSA scan is abnormal.